2022
DOI: 10.24912/ja.v26i3.1067
|View full text |Cite
|
Sign up to set email alerts
|

The Factors Impact On Earnings Management On Indonesia Mining Company

Abstract: This purpose of this research to analyze the impact of size, age, profitability, and leverage on earnings management of the company. The data sampling was selected using a purposive sampling technique to obtain 20 mining companies listed on the Indonesia Stock Exchange IDX that can meet the criteria. The analysis in this study was binary logistic regression analysis through SPSS 26. The analysis found that firm size insignificant effect on earnings management. Company age has a negative and significant impact,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
2
0
1
Order By: Relevance
“…According to (Cudia and Cruz, 2018) and (Lazzem and Jilani, 2018), leverage has a positive and significant relationship with earnings management. However, (Hutauruk et al, 2022), (Ghofir and Yusuf, 2020), and (Santoso, 2023) concluded otherwise, that leverage has no significant impact on earnings management. According to these studies, the following hypothesis was developed:…”
Section: Figure 3 Forms Of Tax Incentivesmentioning
confidence: 99%
“…According to (Cudia and Cruz, 2018) and (Lazzem and Jilani, 2018), leverage has a positive and significant relationship with earnings management. However, (Hutauruk et al, 2022), (Ghofir and Yusuf, 2020), and (Santoso, 2023) concluded otherwise, that leverage has no significant impact on earnings management. According to these studies, the following hypothesis was developed:…”
Section: Figure 3 Forms Of Tax Incentivesmentioning
confidence: 99%
“…Terjadi hasil yang berbeda yang dilakukan pada penelitian lain Purnama dan Taufiq (2021) serta Swai (2016) firm size signifikan negatif pada earning management. Namun, bertolak belakang dengan penelitian sebelumnya yang dilakukan oleh Cudia dan Dela Cruz (2018), Rasyid (2021), Hutauruk et al (2022), dan Suheny (2019) mengatakan bahwa firm size tidak berpengaruh signifikan pada earning management.…”
Section: Pendahuluan Latar Belakangunclassified
“…Liquidity reflects the availability of funds the company owns to meet all debts that will mature. Liquidity is the fulfilment of financial obligations that must be repaid immediately (Hutauruk et al, 2022). Liquidity is a financial ratio in meeting short-term obligations by linking the amount of cash and other assets with short-term liabilities.…”
Section: Introductionmentioning
confidence: 99%